The Use of Canva Application on Material of Advertising Text - Avifa Choirunisa; Ahmad Fadly (Universitas Pendidikan Ganesha, 2023)
Students' understanding of Indonesian language learning, especially in advertising texts, was low. They had difficulty in understanding and processing the information in the advertising text using only limited learning media. Therefore, a solution is needed to optimise the effectiveness of advertising text learning. The Canva application can be used to solve this problem. The purpose of this research was to help teachers and students explore and facilitate the learning of advertising text material by helping students understand advertising text through visual representations made with The Canva application. The subjects of this study were 8th grade students. This research used descriptive qualitative methods with data collection techniques through observation, interviews, and questionnaires, as well as data reduction and data analysis techniques. The result of this study was that the use of Canva application media in learning Indonesian advertising text was considered effective and interesting by 100% of students who were used as research subjects. Students easily understand advertising text learning material after using Canva, which increases student involvement in the learning process.